Charity and Education: Lutheran Social Initiatives in Modern Northeast China - QIU Guangjun, (Journal of Research for Christianity in China (JRCC), 2025)
The Lutheran Church conducted missionary activities in Northeast China for over half a century during the modern era. While developing its religious work, the Lutheran Church also engaged in social undertakings such as education, healthcare, and charity. These endeavors not only advanced the church's mission but also exerted a positive influence on Northeast society.
Keywords: Lutheran Church Modern Northeast China Social Welfare